BRIDGING A GAP IN THE GREATER SUNDA: FIRST RECORD OF YELLOW-BREASTED FLOWERPECKER PRIONOCHILUS MACULATUS IN BANGKA ISLAND, SUMATRA - Iqbal, Muhammad (CONSERVA, 2025)
The Yellow-breasted Flowerpecker Prionochilus maculatus is a species of flowerpecker found in Southeast Asia, Sumatra and Kalimantan. This species has never been recorded in Bangka Island, Sumatra. On June 4 2022, this species was documented in Kemuja Village (02°05'07"S, 105°59'18"E), Mendo Barat Subdistrict, Bangka District, Bangka Belitung Province, Sumatra, Indonesia. This observation is represent the first record of the Yellow-breasted Flowerpecker on Bangka Island, and this is a bridge from the discontinuous distribution between its distribution in Southeast Asia, Sumatra and Kalimantan.